Project Based Learning in Online Discussion Forums and Self-Regulated Learning - Marnola, Ilham; Degeng, I Nyoman S.; Ulfa, Saida; Praherdhiono, Henry (Al-Hayat: Journal of Islamic Education, 2024)
This research aims to explain how students' problem solving abilities differ using project-based learning strategies in online discussion forums and conventional learning. It focuses on how problem-solving abilities differ between low- and high-independent learning students. The interaction of learning strategies and independent learning will also discuss the impact on problem-solving skills. In this research, a quantitative approach was used, with a quasi-experimental approach, namely a nonequivalent control group design. The population of the study was 140 students. The number of samples involved was 71 people. Data collection techniques use self-regulated learning questionnaire instruments and problem solving test instruments. The data analysis technique uses two-way 2 x 2 analysis of variance (Anova). The research results show that students who use the PjBL learning strategy in online discussion forums have different problem-solving abilities than those who use conventional learning methods. Students who use the PjBL learning method in online discussion forums are better than students who use conventional learning methods. The problem solving abilities of students with low and high self-regulated learning are different. Students with high self-regulated learning have better problem solving skills than students with low self-regulated learning. There is a relationship between self-regulated learning strategies and problem solving abilities. This shows that PjBL learning strategy variables influence problem solving skills in online discussion forums and independent learning. This research can be a valuable alternative to support student learning in higher education by utilizing technology. Educators also need to strengthen students' self-regulated learning to maximize learning outcomes.